Strategi Komunikasi Antara Pengasuh Dengan Peserta Didik Dalam Meningkatkan Hafalan Al-Qur’an Dirumah Tahfidz Mardhatillah Nagari Tabek Patah Kecamatan Salimpaung Kabupaten Tanah Datar - Vivi Fajmela; Yusuf Afandi (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This study aims to determine the stages of communication strategies and effective communication strategies owned by caregivers at the Tahfidz Mardhthillah Nagari Tabek Patah House, Salimpaung District, Tanah Datar Regency, West Sumatra Province. The research was conducted using descriptive qualitative methods, namely explaining objectively about how communication between caregivers and students improves memorization at the home of Tahfidz Mardhatillah Nagari Tabek Patah, Salimpaung sub-district, Tanah Datar district. in the field then poured into the results and conclusions. The results of the study stated that the communication strategies carried out by the caregivers of the Tahfidz Mardhatillah House included students being required to add their memorization at home, memorization that had been implemented had to be deposited first before students continued their memorization to other parts of the letter, caregivers gave rewards to students who had memorized the good one. In addition, the caregivers also give punishment to students who do not want to add their memorization, namely if:one day does not add sanctions for bowing for 5 minutes, then two days will be sanctioned for bowing for ten minutes, and three days sanctioned for bowing for 15 minutes and so on.